2013
DOI: 10.3389/fpsyt.2013.00029
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Nicotinic Acetylcholine Receptors: Common Molecular Substrates of Nicotine and Alcohol Dependence

Abstract: Alcohol and nicotine are often co-abused. As many as 80–95% of alcoholics are also smokers, suggesting that ethanol and nicotine, the primary addictive component of tobacco smoke, may functionally interact in the central nervous system and/or share a common mechanism of action. While nicotine initiates dependence by binding to and activating neuronal nicotinic acetylcholine receptors (nAChRs), ligand-gated cation channels normally activated by endogenous acetylcholine (ACh), ethanol is much less specific with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 236 publications
(310 reference statements)
4
88
0
3
Order By: Relevance
“…4A) in vivo. It has previously been shown that the nonspecific nAChR antagonist MEC (Peng et al, 2013) reduces ethanol consumption and blocks ethanol-induced DA release in the NAc (Blomqvist et al, 1993;Hendrickson et al, 2013). To understand how nAChRs contribute to ethanol's inhibitory effects on DA in the NAc, we evaluated the effects of MEC on evoked DA signals in anesthetized mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4A) in vivo. It has previously been shown that the nonspecific nAChR antagonist MEC (Peng et al, 2013) reduces ethanol consumption and blocks ethanol-induced DA release in the NAc (Blomqvist et al, 1993;Hendrickson et al, 2013). To understand how nAChRs contribute to ethanol's inhibitory effects on DA in the NAc, we evaluated the effects of MEC on evoked DA signals in anesthetized mice.…”
Section: Resultsmentioning
confidence: 99%
“…Often taken in concert (Miller and Gold, 1998), tobacco and alcohol are leading causes of preventable death in the United States (Danaei et al, 2009). Approximately 80% of alcoholics are also smokers (Hendrickson et al, 2013;Taylor et al, 2013b), and heavy smokers are 10 times more likely to be alcoholics (DiFranza and Guerrera, 1990). Although smoking rates in the general population have decreased in recent decades, the use of nicotine has remained high (∼70%-75%) in individuals who regularly use alcohol (Meyerhoff et al, 2006;Hendrickson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies indicate that ethanol potentiates the response of high-affinity nAChRs to both acetylcholine and nicotine. 32 Even small amounts of alcohol are known to boost nicotine effects, inducing subjects to smoke more. A recent study in a mouse model examining the effects of nicotine on cocaine abuse has provided a biological mechanism to support the gateway theory by showing that nicotine increases the expression of the FosB gene (which has been related to addiction) and increases the vulnerability to cocaine dependence.…”
Section: Mechanism Of Action: Neurobiologymentioning
confidence: 99%